Pengaruh Pemberian Pakan Buatan, Pakan Alami, dan Kombinasinya terhadap Pertumbuhan, Rasio Konservasi Pakan dan Tingkat Kelulushidupan Ikan Sidat (Anguilla bicolor) [Effect Of Artificial Feed, Natural Feed And Combination Between Them To Growth Rate, Food Convertion Ratio And Survival Rate Of Indonesian Shortfin Eel (Anguilla bicolor) ] - Muhammad Arief; Dwi Kukuh Pertiwi; Yudi Cahyoko (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
Abstract Indonesian shortfin eel (Anguilla bicolor) is one of kind of fish sold in the International markets especially for Japan and Korea, so this fish has the potential as an export commodity. Indonesian shortfin eel has a high nutrient content. Indonesian shortfin eel reached the size of concumption when it is weighted 120-500 grams. The purpose of this research was to know the effect of artifial feed, natural feed and combination between them to growth rate, food convertion ratio and survival rate of Indonesian shortfin eel (Anguilla bicolor). This research used experimental method and Completely Random Design method with five treatments. Each treatment was replicated four times. The result of this research showed that artificial feed, natural feed and combination between them were significantly difference (p<0,05) on growth rate of body wight and food convertion ratio but not significantly difference (p>0,05) on survival rate of Indonesian shortfin eel. The best growth in treatment E (1.72%), then a row followed by treatment A (1.51%), B (1.29%), D (1.25%) and C (1.25%) . The lowest feed conversion ratio obtained in treatment E (6.73) and highest feed conversion ratio obtained in treatment C (9.91). Survival rate obtained was 100%. Water quality of maintenance media of eel was the temperature 28-31°C, pH 7-8,5, dissolve oxygen 3,5-5,8 mg/l and ammonia 0,003 mg/l.